Construction field guide - Thomas, Paul I. (BNi Building News, 2009)
This ready-reference field guide puts every aspect of the construction industry right at your fingertips. It is completely up to date, and its scope of coverage is truly encyclopedic. In a clear, straightforward manner, it explains what's required in contracts and documents, building codes and inspections, labor relations and safety programs, financing and insurance, planning and scheduling, quality control and project management and much, much more. Although Construction Field Guide was originally developed for the general contractor, this new Third Edition has been supplemented to be an invaluable reference for the subcontractor, owner, architect, inspector, property manager, construction attorney and anyone else in the industry. Whether you are dealing with dispute resolution or cost estimating, this book tells you what you need to know, what to do, and how to get it done. Moreover, the Construction Field Guide includes an incredibly detailed description of all construction materials and methods, from site exploration and soil testing, to concrete construction, rough carpentry, lathing and plastering, roofing, painting, glass and glazing, wiring, plumbing, insulation and more. For each topic you'll find a clear description of the materials used, preparation methods, capacities, measurements, and even estimating techniques and considerations. -- Provided by publisher.
"Architects, constructors, engineers."
Keywords: Contractors' operations -- Handbooks, manuals, etc.; Construction industry -- Management -- Handbooks, manuals, etc.; Construction contracts -- Handbooks, manuals, etc.; Building materials -- Handbooks, manuals, etc.; elektronické knihy; electronic books